2018
DOI: 10.1002/1873-3468.13250
|View full text |Cite
|
Sign up to set email alerts
|

Probing the interaction of a quercetin bioconjugate with Bcl‐2 in living human cancer cells with in‐cell NMR spectroscopy

Abstract: In-cell NMR spectroscopy has emerged as a powerful technique for monitoring biomolecular interactions at an atomic level inside intact cells. However, current methodologies are inadequate at charting intracellular interactions of nonlabeled proteins and require their prior isotopic labeling. Herein, we describe for the first time the monitoring of the quercetin-alanine bioconjugate interaction with the nonlabeled antiapoptotic protein Bcl-2 inside living human cancer cells. STD and Tr-NOESY in-cell NMR methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 54 publications
(90 reference statements)
1
42
0
Order By: Relevance
“…Further, molecular docking experiments suggest that anti-apoptotic BCL2 family proteins (BCL2, BCL-xl and MCL1) could be directly inhibited by quercetin (Figure 9 and Table 2). A recent study showed that a quercetin–alanine conjugate directly binds to BCL2 and enhances apoptosis [61]. We believe that a similar interaction may be at play here.…”
Section: Discussionsupporting
confidence: 53%
“…Further, molecular docking experiments suggest that anti-apoptotic BCL2 family proteins (BCL2, BCL-xl and MCL1) could be directly inhibited by quercetin (Figure 9 and Table 2). A recent study showed that a quercetin–alanine conjugate directly binds to BCL2 and enhances apoptosis [61]. We believe that a similar interaction may be at play here.…”
Section: Discussionsupporting
confidence: 53%
“…Such observations could be attributed to the off-target binding in a multiple target environment. In addition to the target-observed in-cell NMR, the ligand-observed NMR can also be performed in vivo [164]. Donatella Potenza et al had conducted STD and trNOE experiments to validate the binding of specific compounds to integrin αvβ3 in ECV304 cells [165].…”
Section: In-cell Nmrmentioning
confidence: 99%
“…As FAAH is a membrane protein, the assay is feasible using this system, and compound fragments which were able to inhibit its activity were screened and confirmed [136]. The molecular interactions between Bcl-2 and the quercetin-alanine bioconjugate were investigated using proton-based NMR experiments [104]. This study shows that ligand-based NMR such as STD is also applicable in in-cell NMR.…”
Section: In-cell Nmr In Drug Discoverymentioning
confidence: 99%